PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING PADA GURU DI SMK NEGERI 4 KLATEN - Surono . (STIE AUB Surakarta, 2014)
The purpose of this study is investigate influence of leadership and organization commitment to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten. The Hypothesis which have been formulated in this research is: there is influence of leadership and organization commitment to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten The research is a survey to the teacher of The Government Vocational High School 4 at Klaten. Data of this researh is primary. Data have been collected with quesionary was processed with, assumption of regression test, the moderated regression analysis, t test, F test and test of R2 The t test have been done in this research show that leadership and organization commitment have influence to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten as partial. The F test have been done show that the leadership and organization commitment have influence to teacher perfomance with job satisfaction as moderating at The Government Vocational High School 4 at Klaten as simultance. Keyword: leadership,organization commitment,perfomance, job satisfaction